Analisa Faktor Penyebab Kejadian Stunting di Wilayah Kerja Puskesmas Sukmajaya: Analysis of Factors Causing Stunting Incidents in the Sukmajaya Community Health Center Working Area - Sari, Agustina; Kurnia, Anggraeni; Kartini, April Lia; Arafat, Prasda Fakih; Taupik, Taupik (Journal of Public Health Education, 2023)
Background: Stunting is a chronic nutritional deficiency issue resulting from prolonged insufficient nutrient intake, leading to growth impairment in children, where their height is lower or shorter than the standard for their age. One of the preventive measures for stunting focuses on a family-based approach, as the family is the first environment introduced to the baby. The first two years of a child's life, known as the first 1,000 days, are critical for their growth and development. During this period, infants must receive sufficient and appropriate nutritional intake to avoid malnutrition, which can lead to stunting. Exclusive breastfeeding for the first 6 months supports the baby's growth in the initial 6 months of life. Objective: To understand the overview of stunting cases regarding the compliance of mothers in providing exclusive breastfeeding to their infants in the Sukmajaya Health Center in 2022. Method: This research employs a descriptive analytical method with the population consisting of the entire community in the Sukmajaya Health Center's service area and a sample of 41 respondents. The research instrument used is through direct observation with interview methods and the collection of secondary data through the annual reports of the Sukmajaya Health Center, the Health Profile of Depok City, and several journals from previous studies. Data analysis is descriptive using the Matrix Criteria Method. Results: The research results indicate that out of 39 stunted children, 28 parents stated that they did not exclusively breastfeed their infants. Other factors influencing stunting in children include low birth weight, unbalanced complementary feeding intake, and incomplete immunization. Conclusion: Calculations regarding problem priorities show that addressing the issue through the creation of an Electronic Module to enhance mothers' knowledge and understanding of exclusive breastfeeding and its long-term effects on a child's future is necessary.